2017
DOI: 10.1016/j.jesf.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of suspension training for trunk muscle power in Sanda athletes

Abstract: The aim of this study was to investigate whether both suspension training (ST) and traditional training (TT) can improve Sanda athlete's strength quality of trunk muscles and to explore the effect of suspension training on Sanda athletes' trunk muscle power production. Twelve elite Sanda athletes from the Competitive Sports School of Shanghai University of Sport were randomly assigned to experimental group (EG) and control group (CG). EG and CG were regularly trained with suspension training and traditional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Handgrip strength has been strongly linked to lower limb muscle power, torsion and extension of the knee, and the transverse muscles of the calf [36]. Max et al in a study carried out in Sanda athletes concluded that compared with traditional core strength training methods, suspension training can improve the explosive power of trunk extension and flexion muscles [33]. In our study, the HIIT group achieved significant improvements in handgrip strength after the intervention.…”
Section: Discussionsupporting
confidence: 52%
“…Handgrip strength has been strongly linked to lower limb muscle power, torsion and extension of the knee, and the transverse muscles of the calf [36]. Max et al in a study carried out in Sanda athletes concluded that compared with traditional core strength training methods, suspension training can improve the explosive power of trunk extension and flexion muscles [33]. In our study, the HIIT group achieved significant improvements in handgrip strength after the intervention.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, a recent systematic review including 16 studies showed higher activation of core muscles for ST compared with PRT in the pushup, inverted row, prone bridge, and hamstring curl exercises (Aguilera-Castells and Busca, 2018). Regarding the chronic effects of ST, Ma et al (2017) showed higher increases in core muscle strength and power for ST compared with PRT. Furthermore, Maté-Muñoz et al (2014) compared the effects of PT and ST performed with the same exercises and maximal velocities.…”
Section: Suspension Training As a New Approach To Optimize Improvemenmentioning
confidence: 94%
“…Results showed that ST is as effective as PT for improving the strength, power and movement velocity. However, these studies were performed with young (Maté-Muñoz et al, 2014) and trained cohorts (Ma et al, 2017). Therefore, future studies should investigate the effects of ST in older adults.…”
Section: Suspension Training As a New Approach To Optimize Improvemenmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, performing prone and supine bridges on a whole-body vibration platform induces higher trunk muscle activity compared with performing the same exercise on the floor [ 14 ]. However, research on the muscle activity during prone bridge exercises with feet on the suspension straps is limited [ 15 ], although previous studies have reported the use of suspension training in athletic populations, such as synchronized swimming [ 16 ] and Chinese boxing [ 17 ], and in clinical patients with brain injury [ 18 ] and functional training in older adults [ 19 ].…”
Section: Introductionmentioning
confidence: 99%